نموذج مقترح لنظم الشراكة مع القطاع الخاص في مجال الاستثمار الرياضي بالاتحادات الرياضية المصرية - عثمان، ليلى عثمان إبراهيم; سعودي، أسامة رجب عبدالمعبود عبدالعزيز; الشحات، محمد إبراهيم علي (جامعة بنها - كلية التربية الرياضية للبنين, 2022)
يهدف البحث إلى وضع نموذج مقترح لتطبيق نظم الشراكة مع القطاع الخاص في مجال الاستثمار الرياضي بالاتحادات الرياضية المصرية. واستخدم الباحث المنهج الوصفي بخطواته وإجراءاته باستخدام الأسلوب المسحي نظر لملائمته لطبيعة عينة البحث. وتكونت عينة البحث بالطريقة العمدية وقوامها (١٨٠) مسئول، تم إجراء الدراسة الأساسية على عينة قوامها (١٥٠) مسئول، كما تم إجراء الدراسة الاستطلاعية على عينة قوامها (30) مسئول من نفس مجتمع البحث وخارج العينة الأساسية. وكانت أهم أدوات جمع البيانات هي مقياس نموذج مقترح لنظم الشراكة مع القطاع الخاص في مجال الاستثمار الرياضي بالاتحادات الرياضية المصرية. وفي ضوء نتائج البحث توصل الباحث إلى الاستخلاصات والتوصيات الأتية: 1-أن مجلس إدارة الاتحاد يدرك الدور الذي تلعبه الشراكة مع القطاع الخاص في تحسين الخدمات المقدمة للمستفيدين. 2-أن الشراكة مع القطاع الخاص للاستثمار الرياضي من أولويات الاتحاد. The research aims to develop a proposed model for the application of partnership systems with the private sector in the field of sports investment in the Egyptian sports federations. The researcher used the descriptive approach with its steps and procedures using the survey method due to its suitability to the nature of the research sample. The research sample was formed by the intentional method and consisted of (180) officials, the basic study was conducted on a sample of (150) officials, and the exploratory study was conducted on a sample of (30) officials from the same research community and outside the basic sample. The most important data collection tool was a proposed model scale for partnership systems with the private sector in the field of sports investment in Egyptian sports federations. In light of the research results, the researcher reached the following conclusions and recommendations: 1- The Federation’s Board of Directors is aware of the role that partnership with the private sector plays in improving services provided to beneficiaries. 2- The partnership with the private sector for sports investment is one of the priorities of the Federation. 3- The conviction that investing in sports institutions is a source of income for both the sports institution, the state and the investor. 4- The legislative authority (the People's Assembly, the Shura Council) to propose a law that places the sports field within the investment fields.
Keywords: المؤسسات الرياضية -- الاستثمارات الرياضية -- الإدارة الرياضية -- القطاع العام -- القطاع الخاص -- القوانين والتشريعات